Teacher's creative competence - Anna Babicka; Przemysław Dudek; Małgorzata Makiewicz; Elżbieta Perzycka (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This article's aim is to study what 180 Polish teachers understand by creativity and how they put it into practice. The Creative competency of teachers was evaluated, using 6 variables: 1) understanding of teaching as a creative action; 2) knowledge of opportunities and secure limits in implementing creative changes; 3) ability to create and change elements of classroom work; 4) understanding of educational entities and having the ability to act in order to increase the autonomy of such entities; 5) critical thinking; 6) ability to research their own practice. To do so both a semi-structured interview and direct observation in their classroom were utilized. Results point out the need to foster teachers' innovative and creative capabilities.